Analisis Perbandingan Pengaruh Likuiditas, Solvabilitas, dan Profitabilitas Terhadap Harga Saham pada Perusahaan LQ 45 - Christine Dwi Karya Susilawati (Jurnal Akuntansi, 2012)
Analysis tool commonly used is ratio analysis. This study uses three ratio analysis, the liquidity ratio is represented by the Current Ratio (CR), solvability ratio represented by the Debt Equity Ratio (DER), and profitability ratios are represented by the Return On Assets (ROA). This study aims to determine & analysis the significant influence of financial performance in the liquidity, solvability and profitability ( CR, DER, and ROA) to the stock price index of LQ45. The sample used as many as nineteen companies who always entered the elections LQ45 period 2006-2009. This study uses the method of hypothesis testing and processed through single linear regression method. The results showed that , solvability and profitability ( DER & ROA) significantly influence stock prices. The higher influence to stock price is ROA as indicator of profitability with R square 40,2%.